Velocities of dual homothetic exponential motions in D3 - Asil, V. (Shiraz University, 2007)
In this paper the concept of Homothetic Dual Exponential Motions in D 3 is discussed and their velocities obtained. Due to the way in which the matter is presented, the paper gives some formula and facts about dual exponential motions which are not generally known. © Shiraz University.
Keywords: Dual number; Dual vector; Exponential transformation; Homothetic motion